Petrologia do plúton Serra da Macambira, neoproterozóico da faixa seridó, província Borborema (NE do Brasil) - Silva, Dalton Rosemberg Valentim da (2011)
The final stage of Brasiliano/Pan-African orogeny in the Borborema Province is marked by widespread plutonic magmatism. The Serra da Macambira Pluton is an example of such plutonism in Seridó Belt, northeastern Borborema Province, and it is here subject of geological, petrographic, textural, geochemical and petrogenetic studies. The pluton is located in the State of Rio Grande do Norte, intrusive into Paleoproterozoic orthogneisses of the Caicó Complex and Neoproterozoic metassupracrustal rocks of the Seridó Group. Based upon intrusion/inclusion field relationships, mineralogy and texture, the rocks are classified as follows: intermediate enclaves (quartz-bearing monzonite and biotite-bearing tonalite), porphyritic monzogranite, equigranular syenogranite to monzogranite, and late granite and pegmatite dykes. Porphyritic granites and quartz-bearing monzonites represent mingling formed by the injection of an intermediate magma into a granitic one, which had already started crystallization. Both rocks are slightly older than the equigranular granites. Quartz-bearing monzonite has K-feldspar, plagioclase, biotite, hornblende and few quartz, meanwhile biotite-bearing tonalite are rich in quartz, poor in K-feldspar and hornblende is absent. Porphyritic and equigranular granites display mainly biotite and rare hornblende, myrmekite and pertitic textures, and zoned plagioclase pointing out to the relevance of fractional crystallization during magma evolution. Such granites have Rare Earth Elements (REE) pattern with negative Eu anomaly and light REE enrichment when compared to heavy REE. They are slight metaluminous to slight peraluminous, following a high-K calc-alkaline path. Petrogenesis started with 27,5% partial melting of Paleoproterozoic continental crust, generating an acid hydrous liquid, leaving a granulitic residue with orthopyroxene, plagioclase (An40-50), K-feldspar, quartz, epidote, magnetite, ilmenite, apatite and zircon. The liquid evolved mainly by fractional crystallization (10-25%) of plagioclase (An20), biotite and hornblende during the first stages of magmatic evolution. Granitic dykes are hololeucocratic with granophyric texture, indicating hypabissal crystallization and REE patterns similar to A-Type granites. Preserved igneous textures, absence or weak imprint of ductile tectonics, association with mafic to intermediate enclaves and alignment of samples according to monzonitic (high-K calcalkaline) series all indicate post-collisional to post-orogenic complexes as described in the literature. Such interpretation is supported by trace element discrimination diagrams that place the Serra da Macambira pluton as late-orogenic, probably reflecting the vanishing stages of the exhumation and collapse of the Brasiliano/Pan-African orogen.